2013
DOI: 10.21897/rmvz.150
|View full text |Cite
|
Sign up to set email alerts
|

Efecto de la densidad de siembra y la adición de ácido ascórbico en el cultivo de Osteoglossum bicirrhosum

Abstract: RESUMENObjetivo. Evaluar el efecto de la densidad de siembra y la adición de ácido ascórbico en la alimentación de alevinos de O. bicirrhosum, cultivados en jaulas. Materiales y métodos. Se incluyeron 396 alevinos y se distribuyeron en nueve tratamientos, resultado de la combinación de los niveles del factor densidad de siembra: 1pez/5 L; 1pez/10 L y 1pez/15 L y los niveles de ácido ascórbico: 0; 500 y 1000 mg/kg. Los datos obtenidos se evaluaron mediante el análisis de varianza del diseño factorial 32. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
1
1
0
1
Order By: Relevance
“…The best digestibility values and analysis of productive variables were found in treatments with dry hydrolyzed fish viscera due to the biological quality, amino acids, interaction of nutrients and the presence of nonspecific growth factors in this product (1). Also, similarities with other studies reported increases in daily size from 0.06 cm to 0.08 cm, which shows that diets that include dry hydrolyzed cachama viscera can produce growth up to 1.21 cm in two weeks in total length during the initial developmental phase, which is highly important for fish species that are of interest to the fish industry (12).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The best digestibility values and analysis of productive variables were found in treatments with dry hydrolyzed fish viscera due to the biological quality, amino acids, interaction of nutrients and the presence of nonspecific growth factors in this product (1). Also, similarities with other studies reported increases in daily size from 0.06 cm to 0.08 cm, which shows that diets that include dry hydrolyzed cachama viscera can produce growth up to 1.21 cm in two weeks in total length during the initial developmental phase, which is highly important for fish species that are of interest to the fish industry (12).…”
Section: Discussionsupporting
confidence: 84%
“…Los mejores valores de digestibilidad y análisis de las variables productivas se encontraron en los tratamientos con extracto seco de hidrolizado de vísceras de pescado, debido a la calidad biológica, composición de aminoácidos, interacción de nutrientes y presencia de factores inespecíficos de crecimiento en esta materia prima (11). De igual manera se presenta similitudes con otros ensayos que reportan incrementos de talla diarios entre 0.06 cm a 0.08 cm., lo que explica que las dietas con inclusiones de extracto seco de hidrolizado de vísceras de cachama pueden alcanzar hasta 1.21 cm quincenales en su longitud total en el desarrollo de su fase inicial, lo cual es de gran importancia para una especie íctica de interés acuariofílico (12).…”
Section: Discussionunclassified
“…This is an important fish species for the fishery because has a relatively large size, which can reach 1.2 m in length and 6 kg in weight, being very used for food by Amazonian riverine populations (Soares et al, 2011;Froese and Pauly, 2019). In addition, it has great potential for aquaculture (Cuaical et al, 2013), and has been used as ornamental fish in aquarium of various part of the world.…”
Section: Introductionmentioning
confidence: 99%